Dynamic Dynamometry to Characterize Disk Turbines for Space-Based Power - Yang, Zhiyuan; Weiss, Hope L.; Traum, Matthew J. (Proceedings of the Wisconsin Space Conference, 2014)
Rankine cycles will someday be the power plants of choice for manned space missions, providing excellent thermodynamic efficiency and high power density. The Rankine cycle’s hallmark is a working fluid that changes phase between liquid and vapor. However, the working fluid must remain in the vapor phase as it passes through the turbine to avoid damaging this component. The need to tightly regulate the working fluid phase through the turbine imposes limits on the power produced and the overall efficiency of the cycle, especially given limitations on power plant volume and mass necessarily imposed by housing it in an interplanetary spacecraft. These limitations could be relaxed if a turbine were incorporated into the Rankine power cycle that was robust and fully operational while processing two-phase flows. Disk turbines have the potential for continuous operation regardless of the thermodynamic quality of working fluid running through them. However, due to high rotational velocity and low torque output by disk turbines, their performance is difficult to evaluate using conventional techniques for aero-derived turbines. To assess disk turbines as candidates for space-based power generation, we describe a method to accurately measure and predict turbine mechanical power output using the rational inertia of the turbine’s spinning components and friction in its bearings as the load. The turbine’s time response to Dirac load inputs, as well as its no-load responses to compressed air input over a range of pressures, are measured. This technique, called dynamic dynamometry, produces turbine power-versus-angular-velocity curves, useful for quantitative performance analysis.